2019
DOI: 10.1177/0022219419893649
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Foundational Reading Skills in Kindergarten: A Curriculum-Based Measurement in Spanish

Abstract: Early identification of learning difficulties is a critical component of the Response to Intervention (RtI) model. In kindergarten, the screening of foundational reading skills can provide a data-based guideline for identifying students requiring a more intensive response-based intervention before starting elementary school. This study examines the classification accuracy and best predictors of a set of Spanish curriculum-based measures administered during kindergarten. The study’s sample included 189 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 74 publications
(112 reference statements)
0
12
0
Order By: Relevance
“…Incorporating additional measures of skills that predict Spanish reading comprehension into the aimswebPlus Spanish reading composite may improve the diagnostic accuracy when predicting student performance on SLA tests. For example, Gutierrez et al (2020) found that decisions made based on a composite score from multiple Spanish early literacy CBMs improved the diagnostic accuracy associated with the measures when predicting reading competency in kindergarten students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporating additional measures of skills that predict Spanish reading comprehension into the aimswebPlus Spanish reading composite may improve the diagnostic accuracy when predicting student performance on SLA tests. For example, Gutierrez et al (2020) found that decisions made based on a composite score from multiple Spanish early literacy CBMs improved the diagnostic accuracy associated with the measures when predicting reading competency in kindergarten students.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we were unable to obtain information regarding the creation of the aimswebPlus Spanish measures from the test developer. Spanish is a syllable‐timed language with a transparent orthography (Gutierrez et al, 2020) and it is unclear whether the aimswebPlus passages were developed to represent that orthography or if they were based on a model of English reading development. If this type of information were available, it would be easier to evaluate the argument that aimswebPlus Spanish CBM‐R performance generalizes to students' Spanish oral reading fluency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect size of the relation between vocabulary and reading comprehension was medium and significant among students ages 6-8 (r = 0.31; k = 9) and 9-12 (r = 0.44; k = 11). We found only one study that examined the relation between vocabulary and reading comprehension for children ages 5-6 (Gutiérrez et al, 2020).…”
Section: Vocabularymentioning
confidence: 99%
“…On the one hand, there are those who may have experienced RD from the beginning of their academic life, who are detected through early evaluation and who, due to this, can count on timely intervention. In this regard, a larger number of studies are usually found that show great advances (Al‐Otaiba et al, 2011; Catts et al, 2015; Gutiérrez et al, 2020; Speece et al, 2011). Despite progress, at least one group of students is routinely missed in this identification process.…”
Section: Introductionmentioning
confidence: 99%